2000
DOI: 10.1007/pl00013928
|View full text |Cite
|
Sign up to set email alerts
|

Morphology and Biomass Allocation of Current-year Shoots of Ten Tall Tree Species in Cool Temperate Japan

Abstract: Variations in morphology and biomass allocation of current-year shoots were investigated in saplings of ten cooltemperate tall tree species. In all the species, the ratio (leaf mass)/(stem mass) was greater in shorter current-year shoots than in longer current-year shoots. This indicates the presence of shoot differentiation, where shorter currentyear shoots are oriented to light-capture or leaf-display and longer current-year shoots are oriented to crown-expansion or space-acquisition. However, two types of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 47 publications
1
41
0
Order By: Relevance
“…New vegetative shoot growth in apple is mainly composed of shorter lengths (Lauri and Kelner 2001). In many forest trees a considerable number of new shoots can be of very short lengths (Hasegawa and Takeda 2001;Suzuki 2000;Yagi 2000). To our knowledge, this is the first report of this nature for the olive tree, and it indicates that the short-length shoots are an important component of vegetative growth in this species.…”
Section: Discussionmentioning
confidence: 74%
“…New vegetative shoot growth in apple is mainly composed of shorter lengths (Lauri and Kelner 2001). In many forest trees a considerable number of new shoots can be of very short lengths (Hasegawa and Takeda 2001;Suzuki 2000;Yagi 2000). To our knowledge, this is the first report of this nature for the olive tree, and it indicates that the short-length shoots are an important component of vegetative growth in this species.…”
Section: Discussionmentioning
confidence: 74%
“…Accordingly, J. curcas adapt to low light availability by growing toward the light to maintain photosynthesis. The higher leaf display index and leaf area ratio in January 2011 in shade-grown J. curcas indicated resource allocation for optimizing light interception (Yagi & Kikuzawa 1999;Yagi 2000). Matos et al (2009) showed that J. curcas grown in shade had higher leaf area and leaf chlorophyll content.…”
Section: Discussionmentioning
confidence: 99%
“…These morphological indices show the distribution of foliage in the plant crown and the optimization of biomass allocation among stems, roots, and leaves (Yagi & Kikuzawa 1999;Yagi 2000;Souza et al 2009). The distribution of foliage also indicates how the plant uses available resources and adjusts to stresses such as drought and shade.…”
Section: Shoot-foliage Relationshipsmentioning
confidence: 99%
“…Measurements of biomass allocations to shoots and leaves followed the methodologies described by Yagi & Kikuzawa (1999), Yagi (2000), and Souza et al (2009b) and were used to identify patterns of biomass allocation and resource optimization within the crowns of species with contrasting leaf phenologies.…”
Section: Shoot-foliage Relationshipsmentioning
confidence: 99%